PERUBAHAN SOSIAL EKONOMI MASYARAKAT DESA KEBOIRENG PASCA PEMBANGUNAN JALUR LINTAS SELATAN (JLS) - Erika Vivian Nurchahyati (Jurnal Ilmiah Dinamika Sosial, 2021)
The government is currently incessantly developing road infrastructure. This development is expected to facilitate community mobility so, that it can help the community's economy. One of these development is Jalur Lintas Selatan(JLS). This southern route is a route that connects all areas in the south of East Java. This development causes social changes in society, especially in social and economic terms. This study uses qualitative research methods using the perspective of Piotr Sztompka's theory of social change. The research subjects were people who lived around the JLS and the research location was in Keboireng Village, Besuki District, Tulungagung Regency. The results of the study were  the existence of JLS has changed the livelihoods of the local community. The change in livelihood was that initially farmers turned into traders on Gemah Beach and Klatak Beach. For social change, it was found that the area traversed by the Southern Passage became noisy and air pollution was encountered due to the large number of vehicles heading for tourist attractions. Keyword : socio-economic change, development, Jalur Lintas Selatan